2017
DOI: 10.1080/16000870.2017.1330454
|View full text |Cite
|
Sign up to set email alerts
|

The contrast between Atlantic and Pacific surface water fluxes

Abstract: The Atlantic Ocean is known to have higher sea surface salinity than the Pacific Ocean at all latitudes. This is thought to be associated with the Atlantic Meridional Overturning Circulation and deep water formation in the high latitude North Atlantic -a phenomenon not present anywhere in the Pacific. This asymmetry may be a result of salt transport in the ocean or an asymmetry in the surface water flux (evaporation minus precipitation; E − P) with greater E − P over the Atlantic than the Pacific. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 53 publications
(124 reference statements)
8
27
0
Order By: Relevance
“…These values are close to the 0.13-0.32 Sv estimated from ocean models, as needed to maintain the salinity balance in the Atlantic Ocean (Zaucker et al, 1994 1812,2021]) of water to the Atlantic and Indian oceans, where it is reincorporated into the water cycle via net E − P . As in previous studies (see Craig et al, 2017, for a synthesis), the freshwater lost in the Indian Ocean is similar to that in the Atlantic Ocean. In these studies, P − E + R is close to zero in the Pacific Ocean, producing a difference of 0.4 Sv between the Atlantic and Pacific oceans.…”
Section: Mean Fluxessupporting
confidence: 80%
“…These values are close to the 0.13-0.32 Sv estimated from ocean models, as needed to maintain the salinity balance in the Atlantic Ocean (Zaucker et al, 1994 1812,2021]) of water to the Atlantic and Indian oceans, where it is reincorporated into the water cycle via net E − P . As in previous studies (see Craig et al, 2017, for a synthesis), the freshwater lost in the Indian Ocean is similar to that in the Atlantic Ocean. In these studies, P − E + R is close to zero in the Pacific Ocean, producing a difference of 0.4 Sv between the Atlantic and Pacific oceans.…”
Section: Mean Fluxessupporting
confidence: 80%
“…The annual mean moisture flux field (Figure 2b) over the Indian Ocean, Maritime Continent, and North‐West Pacific is dominated by JJA, as is Pacific truePE since it is negative during the rest of the year, but strongly positive in JJA, enabling the Pacific basin to be neutral in the annual mean (Figure 3). Emile‐Geay et al (2003) first suggested a role for the Asian Monsoon in the truePE asymmetry but only for the subpolar regions, while Craig et al (2017) showed that the truePE asymmetry is dominated by stronger precipitation per unit area south of 30°N across the Pacific.…”
Section: Seasonal Cycle In Moisture Fluxes and P − Ementioning
confidence: 99%
“…Previous studies have suggested that enhanced northward heat transport in the Atlantic by the Atlantic MOC (Trenberth & Caron, 2001) results in stronger Atlantic evaporation and that the excess water vapor is transported in the Trade Winds across Central America to the Pacific causing weak net evaporation or net precipitation across the Pacific (Broecker, 1991). However, the Atlantic evaporation is only notably stronger in the subpolar region (Craig et al, 2017; Czaja, 2009; Emile‐Geay et al, 2003; Warren, 1983; Wills & Schneider, 2015). There, sea surface temperatures are higher than in the Pacific (Manabe & Stouffer, 1988; Warren, 1983), and a greater fraction of the narrower basin is affected by advection of air off continents with low relative humidity (Schmitt et al, 1989) resulting in stronger area‐averaged evaporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1) to which a small global correction has been applied to ensure global freshwater flux balance, and freshwater fluxes are converted to salt fluxes using a mean ocean salinity of 35 psu. The total surface freshwater flux integrated over the Atlantic basin (between 35 S and 60 N) amounts to a net evaporation of about 0.75 Sv, which is at the upper end of a number of recent estimates (Craig et al 2017). The effect of a potential bias in the freshwater flux over the Atlantic will be discussed in Section 4.…”
Section: Methodsmentioning
confidence: 97%